The Association of Tax Aggressiveness on Accrual and Real Earnings Management - Antonius Herusetya; Cyrilla Stefani (Journal of Accounting and Investment, 2020)
Research aims: This study examines the association of tax aggressiveness and earnings management practices using the accrual and real transaction-based earnings management.Design/Methodology/Approach: We use a purposive sampling method from the manufacturing industry listed on the Indonesia Stock Exchange (IDX) from 2013 to 2017 and obtain a final sample of 500 firm-year observations. Data analysis is conducted using multiple regression models and Stata software.Research findings: Our study finds strong evidence that tax aggressiveness has a positive association with accrual earnings management. Our study also finds contrary evidence that tax aggressiveness has a negative association with real transaction activities at the aggregate level. Further testing found a negative relationship between tax aggressiveness and real transactions at the individual level, i.e., sales manipulation and reduction in discretionary expenses, consistent with our main findings. Theoretical contribution/Originality: Our study extends previous studies on the association of tax aggressiveness using tax shelter prediction model, and aggressive financial reporting using accrual and real transaction-based earnings management. We use tax prediction model in this study as the highest level of tax aggressiveness which is rarely performed in the case of Indonesia.Practitioner/Policy implication: The results of this study provide the implication that to achieve the objectives of aggressive tax reporting and aggressive financial reporting in the same reporting period, managers use accrual and real transaction-based earnings management tools as complementary or substitution to each other.Research limitation/Implication: This study uses Wilson’s (2009) tax shelter prediction model as a proxy of the highest level of tax aggressiveness